Therapeutic Effect of Iron Citrate in Blocking Calcium Deposition in High Pi-Calcified VSMC: Role of Autophagy and Apoptosis - Ciceri, Paola; Falleni, Monica; Tosi, Delfina; Martinelli, Carla; Cannizzo, Stefania; Marchetti, Giulia; D’Arminio Monforte, Antonella; Bulfamante, Gaetano; Block, Geoffrey A; Messa, Piergiorgio; Cozzolino, Mario (International journal of molecular sciences, 2019)
In chronic kidney disease (CKD), the first cause of mortality is cardiovascular disease induced mainly by vascular calcification (VC). Recently, iron-based phosphate binders have been proposed in advanced CKD to treat hyperphosphatemia. We studied the effect of iron citrate (iron) on the progression of calcification in high-phosphate (Pi) calcified VSMC. Iron arrested further calcification when added on days 7–15 in the presence of high Pi (1.30 ± 0.03 vs 0.61 ± 0.02; OD/mg protein; day 15; Pi vs Pi + Fe, p < 0.01). We next investigated apoptosis and autophagy. Adding iron to high-Pi-treated VSMC, on days 7–11, decreased apoptotic cell number (17.3 ± 2.6 vs 11.6 ± 1.6; Annexin V; % positive cells; day 11; Pi vs Pi + Fe; p < 0.05). The result was confirmed thorough analysis of apoptotic nuclei both in VSMCs and aortic rings treated on days 7–15 (3.8 ± 0.2 vs 2.3 ± 0.3 and 4.0 ± 0.3 vs 2.2 ± 0.2; apoptotic nuclei; arbitrary score; day 15; Pi vs Pi + Fe; VSMCs and aortic rings; p < 0.05). Studying the prosurvival axis GAS6/AXL, we found that iron treatment on days 9–14 counteracted protein high-Pi-stimulated down-regulation and induced its de novo synthesis. Moreover, iron added on days 9–15 potentiated autophagy, as detected by an increased number of autophagosomes with damaged mitochondria and an increase in autophagic flux. Highlighting the effect of iron on apoptosis, we demonstrated its action in blocking the H2O2-induced increase in calcification added both before high Pi treatment and when the calcification was already exacerbated. In conclusion, we demonstrate that iron arrests further high Pi-induced calcium deposition through an anti-apoptotic action and the induction of autophagy on established calcified VSMC.